PENGARUH MODEL TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL SISWA SEKOLAH DASAR - B Musticha W; Siti Halidjah; Tahmid Sabri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aim to find out how much the effect use of teams games tournaments has on the results of learning social sciences. The method used in this study was an experimental method, with the design of nonequivalent control group design. The population in this study was all grade V students. The samples in the study were grades V A (26 students) and V B (28 students). The data collection technique used was a measurement technique. The data collection tool used was a test. Based on the data analysis results, the average study results of control class students were 68.65 while the experiment class was 73.21. Hypothetical test results (t-test) using t-test polled variance obtained tcount of 2,,3346 and ttabel table 2.0084 (significant level =5% and dk=(????)68)indicates that thetcount is greater than the table tthen Ha is declared acceptable.. From the calculation of effect size,obtained 0.5555 (moderate criteria) sedang. Thus teams games tournaments have a moderate effect on the results of learning Social Sciences students grade V State Elementary School 12 South Pontianak Keywords : Effect, learning results, social sciences, teams games tournaments.